ENHANCING CYBERSECURITY IN BANKING THROUGH THE IMPLEMENTATION OF BIOMETRIC SYSTEMS: A SYSTEMATIC STUDY - L, Jayasree; Beatrice, B. Anuja (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Security systems in corporations, public spaces, consumer electronics, and private industry are becoming more interested in biometric authentication. Businesses, individuals, and organizations are using biometric security more and more to safeguard their online spaces from attackers and other malicious actors. The term "cyber security" describes the methods, approaches, and instruments used to protect software, computer networks, data, and network systems against potential online threats. The supply of financial services via the internet is known as "cyber banking." Internet banking has expanded along with the shift in the exchange of goods. Internet banking has occasionally experienced problems with security threats, despite its advantages. Biometric security uses behavioral and physical characteristics to authenticate people. It is the most dependable and efficient physical security technique for identity verification. Biometric authentication claims that an individual's unique physical or behavioral characteristics can be used to accurately identify them. To address these concerns, a number of safety measures have been put in place across the board for the Internet banking service. Cybercrime is pervasive throughout the world and represents a serious risk to the development of criminal or terrorist activity. These dangers have the potential to jeopardize both internal and external security if they are not addressed through a single authority. Unnoticed cybercrimes result in the loss of money and personal data. Attacks have previously been launched against information infrastructure and internet services. Hacker attacks and online fraud are just two instances of the frequent crimes involving computers. The Internet of Things, or IoT, is the most dependable platform for enabling pleasant, high-quality human existence. IoT has significantly impacted a number of application sectors. Since smart devices rely on wireless technology for data transit and are developing at a rapid pace, they are more susceptible to hackers. As a result, cybercrime is becoming more commonplace every day. Technology growth gives rise to artificial intelligence (AI)-based cybersecurity, which jeopardizes people's privacy, personal property rights, and public safety. The present study is an attempt to study systematically how the banking security can be impacted through the proper usage of biometric devices integrated with cyber security in banking domain.